2015
DOI: 10.1177/1971400915576658
|View full text |Cite
|
Sign up to set email alerts
|

MRI DWI/ADC signal predicts shrinkage of lumbar disc herniation after O2–O3 discolysis

Abstract: T2-shine through effect in DWI is present before morphological disc reduction and moreover could be considered as a predictive sign of response to oxygen-ozone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
(19 reference statements)
0
23
0
Order By: Relevance
“…We request follow-up MRI only in patients with worsening or changing symptoms to rule out the possibility of a septic discitis or the development of recent discal lesions at different levels. Studies that included both clinical and radiological follow-ups have reported a reduction of herniation volume in 63–96% of the patients at 6-month control [ 25 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We request follow-up MRI only in patients with worsening or changing symptoms to rule out the possibility of a septic discitis or the development of recent discal lesions at different levels. Studies that included both clinical and radiological follow-ups have reported a reduction of herniation volume in 63–96% of the patients at 6-month control [ 25 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10,16 The therapeutic efficacy of oxygen–ozone has been known for over 25 years, and many studies have demonstrated its validity for the treatment of herniated discs. 1,35,7,8…”
Section: Discussionmentioning
confidence: 99%
“…Besides being the most common cause of lumboradicular pain, it is also the most frequent indication for spine surgery. 1–13…”
Section: Introductionmentioning
confidence: 99%
“…The vertebral bodies appear hypointense on T1-weighted and hyperintense on T2-weighted images, especially with fat-saturated T2-weighted images, such as STIR [31]. The signal alterations result from microfractures and hemorrhage within the medullary bone.…”
Section: Osseous Injuriesmentioning
confidence: 95%